Integrated Marketing in Subway Fast Food Restaurant Franchises - Nabila Rizki Amalia; Latif Syaipudin (PT. Islamic Research Publisher, 2023)
Franchising is a business carried out by at least two parties, with a predetermined cooperation agreement. Businesses with this franchise concept are assessed in terms of their impact, which can provide positive or negative benefits. As implemented at the Subway fast food restaurant. However, this is a risk in joint business activities. The negative impact is when one of the parties defaults, but the positive impact is that all burdens and responsibilities can be carried by both parties who carry out the agreement. In marketing efforts in this business concept, it is then important to implement integrated marketing communication efforts or integrated marketing is one of the important factors in a business activity. The basic marketing patterns that can be used are advertising, social media and direct marketing. These three become the basic framework that can be used in integrated marketing communication.